AN EXISTENTIALIST FEMINISM ANALYSIS IN KRISTIN HANNAH’S NOVEL THE WOMEN (2024) - Gusfitrianti, Ranti; Pratama, Yoga; Adinda, Karina; Hidayat, Syarif (Sanata Dharma University, Yogyakarta, 2025)
This study aims to analyze the struggles of women veterans in Kristin Hannah's novel The Women (2024) through the lens of Simone de Beauvoir's existentialist feminism. It focuses on the portrayal of women veterans, particularly Frankie (Frances McGrath) while analyzing the construction of gender roles and the dynamics between men and women within the society. Drawing from De Beauvoir’s seminal work The Second Sex, which critiques the historical marginalization of women as the “Other” in patriarchal societies. It analyzes how the novel critiques patriarchal structures while celebrating women's resilience and agency. A descriptive qualitative method emphasizing narrative analysis provides a comprehensive understanding of Frankie's emotional journey and the broader societal issues faced by women veterans. Frankie’s experiences during and after the Vietnam War highlight the marginalization and lack of recognition faced by women veterans. Her journey illustrates core existentialist feminist principles, including the rejection of patriarchal norms and the assertion of self-definition. The study underscores the novel's depiction of women’s solidarity and mutual support as tools for resisting oppression and reclaiming identity. By emphasizing the relevance of De Beauvoir’s philosophy, this research contributes to feminist literary studies, encouraging a reevaluation of patriarchal systems and greater recognition of women’s contributions.